1997
DOI: 10.1093/clinchem/43.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and technical evaluation of ACS™BR serum assay of MUC1 gene-derived glycoprotein in breast cancer, and comparison with CA 15-3 assays

Abstract: The mucin glycoprotein-detecting assay CA 15-3 is a valuable tool for monitoring the course of disease in breast cancer patients. Assays of CA 15-3 are based on the use of two MAbs to polymorphic epithelial mucin (PEM). We evaluated the technical and clinical performance of the Chiron ACSTM BR, an automated competitive chemiluminescence assay using a single MAb, B27.29, and compared the assay’s results with those of the Centocor CA 15-3 RIA, the Abbott IMx CA 15-3, and the Boehringer Mannheim Enzymun-Test CA 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 13 publications
0
20
1
4
Order By: Relevance
“…Secondly, the 13 studies in our analysis used different methods/assays to test CA15-3 and CEA levels, including 11 for CA15-3: MEIA, Abbott AxSYM, ELISA, MyBioSource, Antuos, CIS Bio International, CanAg, Calbiotech, IRMA, CLIA and Bayer, and 8 for CEA: MEIA, Abbott AxSYM, ELISA, Antuos, Quorum, CLIA, Bayer and CanAg. Previous research compared 3 different CA15-3 assay kits (the manual IRMA Centocor and 2 fully automated methods, the ELISA-Boehringer Mannheim-ES300 and the Abbott IMx) and showed that they have different sensitivity and could yield inconsistent results [ 27 , 28 ]. Positive rates of the IRMA CA15-3 did not show any significant variations related to stage, while CA15-3 levels obtained by both ELISA and Abbott assays showed higher values in stage I than in stage II patients [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the 13 studies in our analysis used different methods/assays to test CA15-3 and CEA levels, including 11 for CA15-3: MEIA, Abbott AxSYM, ELISA, MyBioSource, Antuos, CIS Bio International, CanAg, Calbiotech, IRMA, CLIA and Bayer, and 8 for CEA: MEIA, Abbott AxSYM, ELISA, Antuos, Quorum, CLIA, Bayer and CanAg. Previous research compared 3 different CA15-3 assay kits (the manual IRMA Centocor and 2 fully automated methods, the ELISA-Boehringer Mannheim-ES300 and the Abbott IMx) and showed that they have different sensitivity and could yield inconsistent results [ 27 , 28 ]. Positive rates of the IRMA CA15-3 did not show any significant variations related to stage, while CA15-3 levels obtained by both ELISA and Abbott assays showed higher values in stage I than in stage II patients [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, MUC1 is not only overexpressed but also deficiently glycosylated, which leads to the increased exposure of a variable number of immunodominant areas on its peptide core (Burchell and Taylor‐Papadimitriou, 1993). This potentially immunogenic molecule is present in the circulation of carcinoma patients and measurement of its concentration is used to monitor treatment of breast cancer patients (Bon et al , 1997).…”
Section: Peptides and Galnac‐peptidesmentioning
confidence: 99%
“…In breast cancer patients MUC1 serum levels are used to monitor therapy and for early detection of recurrences. 9,10 Proliferative responses to MUC1 and its tandem-repeat peptides have been demonstrated with peripheral blood mononuclear cells (PBMC) of patients with ovarian adenocarcinoma 11 and MUC1 specific cytotoxic T lymphocytes (CTL) have been isolated from tumor-draining lymph nodes of breast 12 and ovarian 13 cancer patients. In patients with ovarian, breast and pancreatic adenocarcinomas cytotoxic T cells can be induced that are specific for the MUC1 tandem repeat.…”
mentioning
confidence: 99%